THE EFFECT OF SALES GROWTH, INFLATION RATE, LIQUIDITY, LEVERAGE, WORKING CAPITAL TURNOVER ON PROFITABILITY IN THE CONSUMER NON CYCLICAL SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019 -2023 - Ng, Martha; Cen, Kelly (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to determine the effect of sales growth, inflation rate, liquidity, leverage, working capital turnover on profitability in the consumer non cyclical sector listed on the Indonesia stock exchange for the period 2019 - 2023. This study uses secondary data. The sample technique in this study used purposive sampling. The number of samples obtained was 62 companies. This research analysis method uses descriptive analysis and several types of evaluations using SmartPLS software assistance. The results of this study indicate that Sales Growth has no effect on profitability. Inflation rate has no effect on profitability. Liquidity has no effect on profitability. Leverage has a negative effect on profitability. Working Capital Turnover has no effect on profitability. Penelitian ini bertujuan untuk mengetahui pengaruh pertumbuhan penjualan, tingkat inflasi, likuiditas, leverage, perputaran modal kerja terhadap profitabilitas pada sektor consumer non cyclical yang terdaftar di bursa efek Indonesia periode 2019 - 2023. Penelitian ini menggunakan data sekunder. Teknik sampel pada penelitian ini menggunakan purposive sampling. Jumlah sampel yang diperoleh sebanyak 62 perusahaan. Metode analisis penelitian ini menggunakan analisis deskriptif serta beberapa jenis evaluasi dengan menggunakan bantuan software SmartPLS. Hasil penelitian ini menunjukkan bahwa Pertumbuhan Penjualan tidak berpengaruh terhadap profitabilitas. Tingkat Inflasi tidak berpengaruh terhadap profitabilitas. Likuiditas tidak berpengaruh terhadap profitabilitas. Leverage berpengaruh negatif terhadap profitabilitas. Perputaran Modal Kerja tidak berpengaruh terhadap profitabilitas.